2000
DOI: 10.1093/jexbot/51.347.1027
|View full text |Cite
|
Sign up to set email alerts
|

A nitric oxide burst precedes apoptosis in angiosperm and gymnosperm callus cells and foliar tissues

Abstract: Leaves and callus of Kalanchoë daigremontiana and Taxus brevifolia were used to investigate nitric oxide-induced apoptosis in plant cells. The effect of nitric oxide (NO) was studied by using a NO donor, sodium nitroprusside (SNP), a nitric oxide-synthase (NOS) inhibitor, N:(G)-monomethyl-L-arginine (NMMA), and centrifugation (an apoptosis-inducing treatment in these species). NO production was visualized in cells and tissues with a specific probe, diaminofluorescein diacetate (DAF-2 DA). DNA fragmentation was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
0
6

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(68 citation statements)
references
References 40 publications
1
61
0
6
Order By: Relevance
“…All these results together suggest that genes regulated by ethylene and ROS are important modulators of plant PCD. In recent years, NO has emerged as a versatile signalling molecule regulating a myriad of biological processes in plants, including cell death responses [31,32]. We showed that generation of NO is important for the enhancement of AAL-toxin-induced cell death as plants unable to synthesize NO were significantly compromised in the PCD response.…”
Section: Distinct Stages Of the Cell Death Processmentioning
confidence: 88%
“…All these results together suggest that genes regulated by ethylene and ROS are important modulators of plant PCD. In recent years, NO has emerged as a versatile signalling molecule regulating a myriad of biological processes in plants, including cell death responses [31,32]. We showed that generation of NO is important for the enhancement of AAL-toxin-induced cell death as plants unable to synthesize NO were significantly compromised in the PCD response.…”
Section: Distinct Stages Of the Cell Death Processmentioning
confidence: 88%
“…1B): non-enzymatic conversion of nitrite to NO in the apoplast, nitrate reductase (NR)-dependent NO formation, and NOS-like activity that is arginine-dependent (Leitner et al, 2009). Decreased NO synthesis and PCD in the presence of NOS inhibitor suggested the involvement of an NOS-like enzyme in plants, but this enzyme remains enigmatic (Pedroso et al, 2000). One potential candidate for a plant NOS, AtNOA1/RIF1, was subsequently demonstrated not to exhibit NOS activity.…”
Section: No Production In Mammalian and Plant Cellsmentioning
confidence: 99%
“…Fluorescence was visualized by confocal laser microscopy ( Fig. 1) as described (Foissner et al, 2000;Pedroso et al, 2000;Beligni et al, 2002;Yao et al, 2002). As a control, we applied carboxy-2-phenyl-4,4,5,5-tetramethylimidazolinone-3-oxide-1-oxyl (cPTIO), an NO scavenger that does not react with any ROS (Barchowsky et al, 1999).…”
mentioning
confidence: 99%